The virus of corruption during the COVID-19 pandemic - Amann, Wolfgang (Organizational corruption, crime and COVID-19, 2025)
Is there a parallel between a biological virus and corruption? If so, what are the similarities? This chapter details 12 parallels and how the analogy of viewing corruption as a virus can help us understand developments during the Covid-19 pandemic. The chapter equally outlines the structure of our book and which authors contribute what kind of insights. As a consequence, we hope that our book helps catalyze learning and proactively prepare the world for future variants of corruption.